2016
DOI: 10.14507/epaa.24.2510
|View full text |Cite
|
Sign up to set email alerts
|

Educação do campo: Aproximações conceituais e evolução histórica no Brasil

Abstract: Among academic studies it is common to distinguish “rural education” and “countryside education”, from the perspective that the emancipatory practice of the education must be based on the questioning of the individual and its relation with the world.  Therefore, as an objective, this paper will: list differences and proximities through distinct categories of “rural” outside city life, such as remote rural or areas with proximity to the countryside, and; through literary, documental and law reviews, analyze pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The MST defended the need for each camp and settlement to have a school with specific projects for rural education (OLIVEIRA; GARCÍA, 2009). The movement for rural education presents the need to listen to and understand the social, cultural, and educational dynamics of the different groups that form the rural people (BARBOSA, 2017;CONTE;RIBEIRO, 2017;OLIVEIRA;GARCÍA, 2009;SANTOS, 2018;SILVA;PASSADOR, 2016). Oliveira and Garcia (2009, p. 165) claim that:…”
Section: Education Conditions In Rural Settlements In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…The MST defended the need for each camp and settlement to have a school with specific projects for rural education (OLIVEIRA; GARCÍA, 2009). The movement for rural education presents the need to listen to and understand the social, cultural, and educational dynamics of the different groups that form the rural people (BARBOSA, 2017;CONTE;RIBEIRO, 2017;OLIVEIRA;GARCÍA, 2009;SANTOS, 2018;SILVA;PASSADOR, 2016). Oliveira and Garcia (2009, p. 165) claim that:…”
Section: Education Conditions In Rural Settlements In Brazilmentioning
confidence: 99%
“…The data showed that access to education in rural settlements directly depends on public policies for the democratization of education at all levels of education (BARBOSA, 2017;SILVA;PASSADOR, 2016;TARLAU, 2015). Significant advances were observed from the implementation of PRONERA, which effectively contributed to expand the access of children and young people to rural education throughout Brazil, especially in the Northeast Region.…”
Section: Education Conditions In Rural Settlements In Brazilmentioning
confidence: 99%
“…Nesse novo cenário, Caldart (2002); Canário (2008); Cavalcante (2010); Souza (2012); Thapliyal (2013); Ribeiro (2015) e Silva & Passador (2016) identificam um momento de desafio e de reinterpretação do contexto educacional no campo. Contudo, não existem análises descritivas, metaanálises nem revisões sistemáticas atuais que versem especificamente sobre o assunto.…”
Section: Introductionunclassified